Problematik Budaya Literasi Membaca Pada Siswa SMPN 1 Bontonompo Selatan - Karim, Deden Hidayati; Sultan, Sultan; Sakaria, Sakaria (Fakultas Teknik Universitas Negeri Makassar, 2025)
This research aims to describe the problematic reading literacy culture of SMPN 1 South Bontonompo students. The method used in this research is the field research method. This research utilizes qualitative data obtained from interviews with students. The data analysis technique in this research is Miles and Huberman's qualitative data analysis with the stages of data reduction, data presentation, and data conclusion and verification. The results of this study show that the problematic of literacy culture in the family environment is divided into 3 indicators, namely: Parents' education and economy are supporting and inhibiting factors. Reading material is one of the things needed in reading activities. Meanwhile, the problems of literacy culture in the school environment are divided into 4 indicators, namely infrastructure, reading materials, the role of teachers, and school policies.